2021
DOI: 10.1097/brs.0000000000003940
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Bariatric Surgery Prior to Posterior Lumbar Decompression and Fusion in an Obese Population with Degenerative Spondylolisthesis

Abstract: Study Design. Cost-effectiveness analysis. Objective. To determine if bariatric surgery prior to posterior lumbar decompression and fusion (PLDF) for degenerative spondylolisthesis (DS) is a cost-effective strategy. Summary of Background Data. Obesity poses significant perioperative challenges for DS. Treated operatively, obese patients achieve worse outcomes relative to non-obese peers. Concomitantly, they fare better with surgery than with nonoperative measures. These competing facts create uncertainty in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Multivariate regression analyzes revealed that undergoing BS before an elective ACDF was associated with a significantly reduced risk of pulmonary, renal and cardiac complications, sepsis and 90-day readmissions. 68 Other papers supported these results 58 , 91 , 180 although some results questioned the real measured effect of a proper weight loss. 71 , 96 These results, together with the presented literature, suggest that a multidisciplinary strategy could play a key role in obese patients.…”
Section: Discussionmentioning
confidence: 88%
“…Multivariate regression analyzes revealed that undergoing BS before an elective ACDF was associated with a significantly reduced risk of pulmonary, renal and cardiac complications, sepsis and 90-day readmissions. 68 Other papers supported these results 58 , 91 , 180 although some results questioned the real measured effect of a proper weight loss. 71 , 96 These results, together with the presented literature, suggest that a multidisciplinary strategy could play a key role in obese patients.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings are consistent with prior literature suggesting that bariatric surgery is cost‐effective in various other patient populations (46). Bariatric surgery has previously been shown to be cost‐effective or cost saving for patients who have a BMI ≥40 kg/m 2 and degenerative spondylolisthesis or hip OA (40,47,48). Alsumali et al reported RYGB as preferred over LSG for populations with a BMI >40 kg/m 2 , while LSG is preferred when the initial BMI is <40 kg/m 2 (40).…”
Section: Discussionmentioning
confidence: 99%